2017
DOI: 10.7567/apex.10.042701
|View full text |Cite
|
Sign up to set email alerts
|

Single-frequency injection-seeded Q-switched Ho:YAG laser

Abstract: An injection-seeded Ho:YAG laser at 2090 nm with changeable pulse repetition frequency (PRF) is demonstrated. Containing a Ho:YAG nonplanar ring oscillator (NPRO) seed, a slave laser, and a single-pass amplifier, the laser delivered single-frequency pulses with energy ranging from 31.4 to 12.7 mJ. The corresponding pulse duration and PRF varied between 102–215 ns and 150–750 Hz, respectively. To the best of our knowledge, this is the highest PRF ever obtained from a single-frequency Ho:YAG laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Up to 31.4 mJ pulse energy with a 102 ns pulse duration at a PRF of 150 Hz was achieved. 23 In the same year, Zhang et al demonstrated a 2.09 μm injection-locked Q-switching Ho:YAG ceramic master oscillator and twostage amplifiers. Up to 55.64 mJ energy was realized with the PRF of 200 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 31.4 mJ pulse energy with a 102 ns pulse duration at a PRF of 150 Hz was achieved. 23 In the same year, Zhang et al demonstrated a 2.09 μm injection-locked Q-switching Ho:YAG ceramic master oscillator and twostage amplifiers. Up to 55.64 mJ energy was realized with the PRF of 200 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The seed laser is a diode-pumped Tm,Ho:YAG laser whose single-frequency operation is achieved by two Fabry–Pérot etalons. In 2017, Wang et al [ 2 ] described a single-frequency Q -switched Ho:YAG linear folding laser, injection-seeded by a Ho:YAG nonplanar ring oscillator (NPRO). In the same year, Na et al [ 10 ] used the same seed laser to achieve an injection-seeded Ho:YAG laser and increased the repetition rate to 1 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow-line-width pulsed solid-state lasers in the 2 µm eyesafe spectral region are usually used as the lidar emitter in coherent Doppler lidars for wind field measurement or in differential absorption lidars (DIALs) for monitoring the concentrations of gases such as CO 2 and H 2 O [1][2][3][4] . A lidar configuration requires an emitter with high energy to increase the detection range, a long pulse width to improve the spectrum resolution and a narrow line width to enhance the spectral purity [5] .…”
Section: Introductionmentioning
confidence: 99%